SELF-IMAGE ANALYSIS OF FEMALE PRISONERS IN TERMS OF TYPE OF CASES AND CRIMINAL PERIODS - Adelya, Bunga; Sukmawati, Indah (Universitas Negeri Padang, 2020)
This research is motivated by female prisoners who have physical and psychological problems, especially those who are related to self-image such as lack of self-confidence, low self-esteem, low self-acceptance, desperation, stress, and inhibited relationships. This study aims to describe the self-image of female prisoners in terms of types of cases, the self-image of female prisoners in terms of the criminal period, and see the difference in self-image when viewed from the type of case and criminal period. The research method used is a quantitative method ,comparative descriptive type with factorial design. The research subjects in this study were 32 female prisoners in LPKA class IIB Tanjung Pati. The instrument in this study used a self-image scale. Data is obtained by collecting the administering instrument and then processed through statistical techniques to determine the total score, mean, standard deviation, interval scale, frequency, and percentage. To see the difference in self-image in terms of types of cases and criminal periods simultaneously a Variant Analysis ?ANAVA ?technique was applied by using ? SPSS statistical program for windows release 15.0.? The results showed that the self-image of female prisoners is in the high category, the self-image of female prisoners in terms of the types of cases is in the high category, the self-image of female prisoners in terms of the criminal period is in the high category, and there is no significant difference in the self-image of female prisoners when reviewed from the type of case and criminal period simultaneously. The implication of this research is the need for counselors in prison to provide guidance and counseling services to female prisoners. Counselors can help overcome the problems experienced by female prisoners and help prisoners maintain a positive self-image especially those related to self-image.